Assessing the quality of individual credit at military bank – Hai Duong branch = Đánh giá chất lượng tín dụng cá nhân tại Ngân hàng TMCP Quân đội – chi nhánh Hải Dương - Nguyễn, Thị Ngân (2021)
The thesis is written based on the need to assess the quality of individual credit at Military Bank – Hai Duong Branch. One of important goals of the branch is to improve the quality of individual credit, contributing to enhancing the business efficiency. Research objectives of that thesis is to determine criteria to assess the quality of individual credit, to make a study about the situation of individual credit, to judge based on analyzed data, to offer solutions and recommendations for the branch in the next time. To achieve the above objectives, the author used two data collection methods (collecting secondary data from books, another researches/articles and collecting primary data from observation and individual interviews at Military Bank – Hai Duong Branch), data analysis method and case study method (records of customers with overdue debts). Using the above methods in the thesis, the author assessed advantages (the annual growth of total individual outstanding, various credit structure, flexible credit policies and credit process, efficient information management and debt classification) and disadvantages (fluctuations in the rate of indviduals‟ overdue debts, ineffective credit monitoring, shortcomings in information collection) in the quality of individual credit at the branch. Based on judgements about the quality of individual credit, the author offered solutions and recommendations for promoting advantages and overcoming disadvantages in individual credit improvement, information collection and use, overdue debt handling customers‟ repayment capability assessment, credit inspection and monitor and so forth.